2010
DOI: 10.1590/s0102-695x2010005000050
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of plant development, morphology and flavonoid content in different cultivation treatments of Calendula officinalis L: , Asteraceae

Abstract: RESUMO:O objetivo deste estudo foi avaliar a influência dos tratos culturais no desenvolvimento vegetal, morfologia e teor de flavonóides para Calendula officinalis L., Asteraceae. Os tratos culturais foram: calagem (CA), calagem + adubação orgânica (CAO) e calagem + adubação química NPK (CAQ). O experimento foi inteiramente casualizado com sessenta repetições e a comparação das médias realizada por ANOVA e teste de Duncan (significância de 95%). Os resultados apontam que CAO e CAQ apresentaram maior desenvolv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 3 publications
0
11
0
1
Order By: Relevance
“…Growth and quality of medicinal plants were shown to be strongly affected by soil conditions and amendments of earthworm-worked compost (vermicompost) and other composts increased the growth and flower production of Calendula (Contreras et al 1994, Paim et al 2010) and other ornamental plant species (Lazcano and Dominguez 2010). It remains to be investigated whether earthworms and/or AMF also evoke changes in the chemical quality of plants as observed for vermicompost for horticultural plants (Zaller 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Growth and quality of medicinal plants were shown to be strongly affected by soil conditions and amendments of earthworm-worked compost (vermicompost) and other composts increased the growth and flower production of Calendula (Contreras et al 1994, Paim et al 2010) and other ornamental plant species (Lazcano and Dominguez 2010). It remains to be investigated whether earthworms and/or AMF also evoke changes in the chemical quality of plants as observed for vermicompost for horticultural plants (Zaller 2007).…”
Section: Discussionmentioning
confidence: 99%
“…1a, b). Paim et al [22] also obtained the highest flowers number from the combination with the Liming+organic fertilizer, but on the other hand, the flowers obtained from the combination with Liming were larger. They noted that the analyzed treatments did not significantly influenced the flowers biomass.…”
Section: Resultsmentioning
confidence: 96%
“…The PRP SOL application led to a significant increase in the height of plants, as compared with the control group. In the Paim et al [22] study calendula plants positively react to liming. Authors obtained the tallest calendula plants (44.1 cm) when liming was applied in combination with an organic fertilizer.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…to have important effects on essential oil contents in C. officinalis flowers (Okoh et al, 2008). In studies on essential oil in different regions and conditions, it was found that essential oil contents in Calendula flowers varied between 0.04% and 0.97% (Okoh et al, 2007;Gazim et al, 2008;Alves Paim et al, 2010;Berimavandi et al, 2011;Khalid and Silva, 2012;Ourabia et al, 2019). The aforementioned studies were carried out in different regions, soil and climate conditions.…”
mentioning
confidence: 99%